1983
DOI: 10.1084/jem.158.3.670
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interferon-gamma as the lymphokine that activates human macrophage oxidative metabolism and antimicrobial activity.

Abstract: Human blood mononuclear leukocytes stimulated with toxoplasma antigen, concanavalin A, mezerein plus lentil lectin, or staphylococcal enterotoxin A secreted a factor (macrophage-activating factor, or MAF) that enhanced the capacity of human macrophages to release H2O2 and to kill toxoplasmas. The same lymphoid supernatants contained IFN gamma but not IFN alpha or IFN beta. The MAF activity of six of seven unfractionated supernatants was completely eliminated by a monoclonal antibody that neutralizes IFN gamma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
879
0
21

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,760 publications
(944 citation statements)
references
References 51 publications
44
879
0
21
Order By: Relevance
“…The finding that rRIFN-y had no effect in vitro, at least not during the culture period of 3 days employed in the current study, suggests that the in vivo effect was indirect; possibly mediated by an activated immune system combined with an enhanced susceptibility of the tumour (Ball et al, 1986;Feinman et al, 1986). This putative involvement of the immune system may be an explanation for the discrepancy between the effect of rRIFNv (Nathan et al, 1983) and may have contributed to the low number of liver metastases and the improved survival found in the current experiments.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…The finding that rRIFN-y had no effect in vitro, at least not during the culture period of 3 days employed in the current study, suggests that the in vivo effect was indirect; possibly mediated by an activated immune system combined with an enhanced susceptibility of the tumour (Ball et al, 1986;Feinman et al, 1986). This putative involvement of the immune system may be an explanation for the discrepancy between the effect of rRIFNv (Nathan et al, 1983) and may have contributed to the low number of liver metastases and the improved survival found in the current experiments.…”
mentioning
confidence: 50%
“…In addition, a number of immunological functions influenced by IFN-y may synergize with this direct cytotoxic action. It has been demonstrated that IFN-y can enhance monocyte cytotoxicity (Kleinerman et al, 1985), macrophage activity (Nathan et al, 1983) and natural killer (NK) cell activity (Weigent et al, 1983). Furthermore, IFN-y can enhance the expression of surface antigens on tumour cells (Pfizenmaier et al, 1985) and on cells of the immune system, i.e.…”
mentioning
confidence: 99%
“…* Significantly different compared with the non-infected control cultures (Student's t-test). down-regulated by parasitic infection, thus abrogating IFN-gmediated activation of macrophages by CD4 þ and CD8 þ T lymphocytes for anti-microbicidal activity against intracellular parasites [29]. Additionally, lysis of T. gondii-infected APC by cytotoxic CD4 þ [30] and CD8 þ [31] T lymphocytes may also be avoided by decreasing the antigen-presenting capacity of infected macrophages, while cytolytic activity in the absence of MHC restriction as described for a Toxoplasma-specific CD8 þ T cell clone [32] would not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Activated macrophages are able to kill Tox. gondii in vitro, and this killing seems to be associated with the ability of the macrophages to release reactive oxygen intermediates (ROI) such as superoxide anion, hydrogen peroxide and hydroxyl radical (Nathan et al, 1983;Murray, Spitalny & Nathan, 1985). Studies have shown that cationic electron carriers, which are thought to undergo redox-cycling and generating superoxide anion and hydrogen peroxide (Hassan & Fridovich, 1979), were able to inhibit intracellular Trypanosoma cruzi and Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%